The mechanisms underlying uterine receptivity in pigs and women - Mohammed, Amal Abdulwahid (2019)
Successful implantation and pregnancy require synchronisation between a fully receptive endometrium and a well-developed embryo. In assisted reproductive technologies (ART), the embryo is created in artificial conditions while endometrial receptivity is affected by ovarian stimulation treatment. Therefore, one or both of these factors may be major contributors to embryo loss. Many supplementation regimes have been utilised to optimise this synchronisation and to provide luteal phase support in ART cycles. In this study, the use of progestogen and oestradiol supplementations in women undergoing ART was assessed using a systematic review and meta-analysis approach. In addition, porcine models were used to evaluate the communication between embryo and endometrium during the peri-implantation period.